Diagnosis of student learning difficulties on learner development studies - Destri Ratna Ma'rifah (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
Learning difficulties could be caused by inside and outside factors of human beings. Learning difficulties could affect student learning success. Learning difficulties should have known from the beginning so that it can be anticipated by educators and learners through the efforts of diagnosis. The aim of this study is to determine the lecture material that is difficult to understand by the students, factors that cause learning disabilities in students, the percentage of students learning difficulties of external factors on Learner development studies. This research is a qualitative descriptive. Qualitative data that obtained to be described to give the real condition. Quantitative data of test results during the middle of the first and the second half used to assist data reduction. The analysis used to adapt from qualitative research, those are data reduction, data presentation, and drawing a conclusion. These results indicate that the material considered the most difficult by the students are the implications of the growth and development of learners. Learning difficulties during learner development studies caused by internal factors such as the physical condition, motivation to learn, how to learn, and social relationships. There are three difficulties external factors affect students learning such as teaching methods, resources and learning materials, lecture hours.